A Collaborative Team Teaching Model for a MSW Capstone Course. Issue 4 (3rd July 2016) - Moore, Rebecca M.; Darby, Kathleen H.; Blake, Michelle E.
Abstract : This exploratory study was embedded in a formative process for the purposes of improving content delivery to an evidence-based practice class, and improving students' performance on a comprehensive exam. A learning and teaching model was utilized by faculty from a three-university collaborative graduate social work program to examine the extent to which course texts and assignments explicitly supported the process, application, and evaluation of evidence-based practices. The model was grounded in a collaborative culture, allowing each faculty to share their collective skills and knowledge across a range of practice settings as they revised the course curriculum. As a result, faculty found they had created a unique community that allowed a wider context for learning and professional development that translated into the classroom. Students enrolled in the revised course across all three universities showed improvement on the comprehensive exam. When faculty themselves invest in collaborative learning and teaching, students benefit.